Analytical and numerical analysis of a ring‐array concentrator. (25th April 2021) - Garcia, Dário; Liang, Dawei; Almeida, Joana; Tibúrcio, Bruno D.; Costa, Hugo; Catela, Miguel; Vistas, Cláudia R.
Summary: The maximum achievable solar concentration of a single reflective primary parabolic mirror is limited by its physical aspect ratio. The maximum concentration of a single refractive Fresnel lens is also largely limited by its chromatic aberration. To resolve these shortcomings, a ring‐array concentrator (RAC) analytical model with variable aspect ratio is proposed here. The concentrator was composed of seven concentric parabolic reflective rings and a small Fresnel lens at the centre. A novel ring height modifier parameter ( h d ) was integrated into the design model, which was complemented with the width of the rings ( d w ), allowing the modification of each individual ring height. Different seven ring models were provided. Concentrated solar flux and optical efficiency were investigated with ZEMAX ray‐tracing software for each model. Over 18 W/mm 2 concentrated solar flux and 54% optical efficiency were numerically achieved for most of these models. Novel ring‐array designs with low total ring surface areas and low aspect ratios were also discussed. The best RAC concentrator configuration was found at d w = 60 mm and h d = 27.5 mm, which showed the highest concentrated solar flux of 18.7 W/mm 2, high optical efficiency of 54.75%, while maintaining a moderate total RAC surface area of 1.81 m 2 and low aspect ratio of 0.50. The solar angle interaction and the associated tracking error were also studied. The proposed RAC model may constitute a very useful tool for designing advanced RACs by considering the strong influence of h d and d w on the key design parameters like concentrated solar flux, optical efficiency, total RAC surface area and aspect ratio. Abstract : Analytical and numerical analysis of a ring‐array concentrator (RAC) with collection area of 3.14 m 2 . The aspect ratio and total surface area of the RAC are found to be intrinsically related to the focal length of the concentrator and to the vertical position of each internal ring. Over 18.72 W/mm 2 concentrated solar flux and optical efficiency 56% are theoretically achievable with a moderate total ring surface area of 7.08 m 2 and at low aspect ratio of 0.33.